(untitled) (Journal Of Educational and Psychological Researches, 2023)
The aim of the research is to examine the multiple intelligence test item selection based on Howard Gardner’s MI model using the Generalized Partial Estimation Form, generalized intelligence. The researcher adopted the scale of multiple intelligences by Kardner, it consists of (102) items with eight sub-scales. The sample consisted of (550) students from Baghdad universities, Technology University, al-Mustansiriyah university, and Iraqi University for the academic year (2019/2020). It was verified assumptions theory response to a single (one-dimensional, local autonomy, the curve of individual characteristics, speed factor and application), and analysis of the data according to specimen partial appreciation of the generalized, and limits its characteristics standard, and the statement of the computerized program outputs (GUMM-2004). Finally, the results verified these assumptions.